Development of an E-Module Based On a Tiered Training Pattern to Improve Problem Solving Skills in Class 5 State Primary School 050661 Kwala Bingai - Adelia Salsabila, Cut; Yuridillah Isnaini, Khoirrun; Antika, Rossila (International Journal of Students Education, 2024)
This research aims to develop a mathematics module with a problem-based learning model that is valid, practical and effective in improving elementary school students' mathematical problem solving abilities. This type of research is research and development ( Research & Development ) which refers to the ADDIE ( Analysis, Design, Development, Implementation, Evaluation ) model. The research instruments used consisted of expert validation sheets, student practicality assessment sheets, and student learning outcome tests. The research results show that a) the e-module developed is suitable for use in mathematics learning based on the overall percentage of media experts 79%, material experts 78%, language experts 77%, and the practicality criteria meets 87% in the very practical category b) based on the results of evaluation tests , e-modules are effective in improving problem solving abilities with a percentage of 80% of students achieving classical completeness. The result of the development is an e-module with a problem-based learning model that is valid, practical and effective for use in mathematics learning.